The Effects of Teamwork, Ethical Sensitivity, Emotion Regulation, and Proactive Personality on Employee Engagement: A Study of Employees at PT Mitra Karya Terkini Shipyard, Sekupang Branch, Batam City, Indonesia - Nur Wahdania; Ramon Zamora; David Panjaitan; Muhammad Rahmat; Rona Tanjung (STIE PEMBANGUNAN TANJUNGPINANG, 2026)
This study analyzes the effect of teamwork, ethical sensitivity, emotion regulation, and proactive personality on employee engagement among employees of PT Mitra Karya Terkini Shipyard, Sekupang Branch, Batam. A quantitative approach was applied to examine the relationships and contributions of the independent variables to the dependent variable. The population comprised 278 employees, and 164 respondents were selected using the Slovin formula at a 5% margin of error. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and were analyzed using multiple linear regression complemented by t-tests, F-tests, and the coefficient of determination (R²). The results show that, partially, teamwork (t = 2.623; sig. = 0.010), ethical sensitivity (t = 2.018; sig. = 0.045), and proactive personality (t = 6.717; sig. = 0.000) have a positive and significant effect on employee engagement, whereas emotion regulation (t = 1.766; sig. = 0.079) has a positive but non-significant effect. Simultaneously, the four variables have a positive and significant effect (F = 85.813; sig. = 0.000) with an Adjusted R² of 67.5%. Proactive personality is the most dominant predictor. These findings confirm that strengthening teamwork, ethical awareness, and proactive behavior can reinforce employee engagement within the organization.